Poor Illness Perceptions Are a Risk Factor for Depressive and Anxious Symptomatology in Fibromyalgia Syndrome: A Longitudinal Cohort Study - de Heer, Eric W.; Vriezekolk, Johanna E.; van der Feltz-Cornelis, Christina M. (Frontiers in Psychiatry, 2017)
Background: Patients with widespread pain, such as in fibromyalgia, are vulnerable for depression and anxiety, which composes a relevant public health problem. Identifying risk factors for the onset of depression and anxiety is therefore warranted. Objective of this study was to determine whether severe pain, maladaptive coping and poor illness perceptions are associated with depressive and anxious symptomatology in fibromyalgia Method: Consecutive patients referred to an outpatient clinic completed sets of physical and psychological questionnaires at baseline and at 18-month follow-up. A total of 452 patients with fibromyalgia syndrome (FMS) were eligible for inclusion, and subsequently, 280 patients returned the baseline questionnaire. Depressive and anxious symptomatology was measured with the Hospital Anxiety and Depression scale (HADS). To measure pain severity, coping style and illness perceptions the Fibromyalgia Impact Questionnaire (FIQ), Pain Coping Inventory (PCI), and the Illness Perception Questionnaire-Revised (IPQ-R) were used respectively. Multivariable logistic regression analyses, bootstrapping and calibration, were performed to examine the association of pain severity, pain coping and illness perception with depressive and anxiety symptoms at follow-up, adjusted for sociodemographic variables. Initial level of depressive and anxiety symptoms were selected as covariates. Results: Mean age was 42.6 years and 95.4% were female. At 18-month follow-up, 68 (of the 195) patients were depressed and 80 (of the 197) were anxious. Only the IPQ-R subscale ‘emotional representations’ showed a significant positive association with depressive symptoms at follow-up (OR=1.10), next to the initial level of depressive symptoms (OR=1.30). In case of anxiety, only the IPQ-R subscale ‘treatment control’ showed a significant negative association with anxiety symptoms at follow-up (OR=.87), next to the initial level of anxiety symptoms (OR=1.45). Conclusion: Our data suggest that not pain severity or maladaptive coping, but poor illness perceptions are important in elevated depressive and anxious symptomatology. Patients with fibromyalgia who think their illness negatively affects their mental well-being are at increased risk for more depressive symptoms, and those who think treatment of their illness will not be effective are at increased risk for more anxiety symptoms. Strengthening illness beliefs and reducing catastrophic thinking, therefore, seem crucial factors in the treatment of patients with FMS.